An Observational Study on Flask Web Framework Questions on Stack Overflow (SO) - Albesher, Luluh; Alfayez, Reem (IET software, 2024)
Web‐based applications are popular in demand and usage. To facilitate the development of web‐based applications, the software engineering community developed multiple web application frameworks, one of which is Flask. Flask is a popular web framework that allows developers to speed up and scale the development of web applications. A review of the software engineering literature revealed that the Stack Overflow (SO) website has proven its effectiveness in providing a better understanding of multiple subjects within the software engineering field. This study aims to analyze SO Flask‐related questions to gain a better understanding of the stance of Flask on the website. We identified a set of 70,230 Flask‐related questions that we further analyzed to estimate how the interest towards the framework evolved over time on the website. Afterward, we utilized the Latent Dirichlet Allocation (LDA) algorithm to identify Flask‐related topics that are discussed within the set of the identified questions. Moreover, we leveraged a number of proxy measures to examine the difficulty and popularity of the identified topics. The study found that the interest towards Flask has been generally increasing on the website, with a peak in 2020 and drops in the following years. Moreover, Flask‐related questions on SO revolve around 12 topics, where Application Programming Interface (API) can be considered the most popular topic and background tasks can be considered the most difficult one. Software engineering researchers, practitioners, educators, and Flask contributors may find this study useful in guiding their future Flask‐related endeavors.